Identification and characterization of MKK6 and AP-1 in Anodonta woodiana reveal their potential roles in the host defense response against bacterial challenge. Issue 124 (May 2022) - Qu, Fufa; Li, Jialing; She, Qing; Zeng, Xuan; Li, Zhenpeng; Lin, Qiang; Tang, Jie; Yan, Yuye; Lu, Jieming; Li, Yumiao; Li, Xiaojie
Abstract: Mitogen-activated protein kinase kinase 6 (MKK6) and activator protein-1 (AP-1) are two of the essential regulatory proteins in the p38 mitogen-activated protein kinase (MAPK) pathway, which participates in the innate immune response to bacterial infections. In this study, molluscan MKK6 ( Aw MKK6) and AP-1 ( Aw AP-1) genes were cloned and identified from Anodonta woodiana . The open reading frame (ORF) of Aw MKK6 encodes for a putative polypeptide sequence of 345 amino acids containing a conserved serine/threonine protein kinase (S_TKc) domain, a SVAKT motif and a DVD domain. Aw AP-1 consists of 294 amino acids including a typical nuclear localization signal (NLS), a Jun domain and a basic region leucine zipper (BRLZ) domain. Quantitative real-time PCR analysis showed that both Aw MKK6 and Aw AP-1 were widely expressed in all selected tissues of A. woodiana and their transcript levels in hemocytes were significantly upregulated when challenged with Aeromonas hydrophila and lipopolysaccharide (LPS). Additionally, the signaling molecules of the Aw MKK6/ Aw AP-1 pathway including Aw TLR4, Aw MyD88, Aw TRAF6, Aw MEKK1, Aw MEKK4, Aw ASK1, Aw TAK1 and Aw p38 mRNA expression showed a stronger responsiveness to LPS challenge in hemocytes of A. woodiana . RNA interference (RNAi) experiments indicated that the silencing of Aw MKK6 or Aw AP-1 could decrease the mRNA expression levels of immune effectors ( Aw TNF, Aw LYZ and Aw Defense). Subcellular localization studies suggested that Aw MKK6 and Aw AP-1 were distributed throughout the cells and nucleus, respectively, and their overexpression could significantly enhance the transcriptional activities of AP-1-Luc in HEK293T cells. These findings suggest that MKK6 and AP-1 play a major role in the host defense response to bacterial injection, which may make contributions to a better understanding of the immune function of the p38 MAPK pathway in mollusks. Highlights: The first experimental evidence for presence of functional Aw MKK6 and Aw AP-1 in Anodonta woodiana. Transcript levels of Aw MKK6 and Aw AP-1 in hemocytes could be significantly induced by A. hydrophila and LPS challenges. Aw MKK6 and Aw AP-1 were involved in the regulation of the expression of Aw TNF, Aw LYZ and Aw Defense. Overexpression of Aw MKK6 and Aw AP-1 could enhance transcriptional activities of AP-1 reporter gene in HEK293T cells.